Case Report: Atrial baffles of pulmonary and systemic veins for the anatomic and physiologic repair of left atrial isomerism heterotaxy—pre- and post-operative three-dimensional reconstructions of two mirror-image pediatric hearts - Perens, Gregory; Silberbach, Michael; Frazer, Jeffrey (Frontiers in Cardiovascular Medicine, 2025)
Intra-atrial baffles of pulmonary and systemic venous flows are relatively rarely used but are important surgical procedures for late-presenting d-transposition of the great arteries (D-TGA) or heterotaxy with anomalous venous connections. Atrial baffle surgery is employed less frequently today due to the advent of the arterial switch procedure. Two children presented with mirror-image venous connections in polysplenic heterotaxy and underwent intra-atrial baffle biventricular repairs. Both cases had ipsilateral pulmonary venous connections, interrupted inferior vena cava with azygous continuation, and concordant ventriculo-arterial connections. Furthermore, a single superior vena cava receiving the azygous and hepatic veins connected to the atrium contralateral to the sub-pulmonary right ventricle was present in both cases. Volumetric cardiac imaging using computed tomography and magnetic resonance imaging allowed for the creation of three-dimensional (3D) model reconstructions for pre-operative surgical planning and postoperative assessment of the atrial baffle pathways. The 3D model reconstructions presented here provide improved visualization and understanding of complex surgical atrial baffles.